Dogs (Canis lupus familiaris) as Virus Carrier in Indonesia - Moch Irfan Hadi; Muhammad Yusuf Alamudi; Mei Lina Fitri Kumalasari; Sri Hidayati; Tatag Bagus Prakarsa; Eva Agustina; Muhamad Ratodi; Misbakhul Munir; Eko Teguh Pribadi; Hanik Faizah (Biotropic : The Journal of Tropical Biology, 2018)
A Virus is an individual that cannot be described as an animal or a plant. If animals and plants contain two nucleic acids (DNA and RNA), on the contrary, the virus only has one of them. These nucleic acids can stimulate a complete virus replication cycle. The virus can only replicate and live on a living host if the host is finally dead, then the virus will move on the cells that are still alive. The virus has genetic material which is a protective protein coat called a capsid. Viruses can infect various varieties of organisms, both eukaryotes (animals, plants, protists, and fungi) and prokaryotes (bacteria and archaea). The Virus infects bacteria known as bacteriophage (phage). The Virus can cause serious diseases for humans such as AIDS, HIV, rabies, etc. Dogs belonging to Canidae family are the sibling of wolves, foxes and raccoon dogs. Among all members of Canidae, dogs have the most closely related to wolves which are the ancestors of dogs. The Canidae family generally has a small elongated body, sharp ear and muzzle, sharp smelling, can run fast and can swim. Dogs are human best friends. While taking care of the dogs, they can be attacked by various diseases. The closeness of the relationship between humans and dogs raises the potential for disease transmission, especially zoonosis and pandemics viruses. Keywords: Canis lupus familiaris, Carier, Influenza, virus